Análise dos Dados de Produção dos Serviços Hemoterápicos do Estado de São Paulo - Alves Fernandes, Maria de Fátima; Barreira Corado de Souza, Leidiana; Camargo Monteiro, Mary; Cardoso Botega, Regina Lúcia; Roque Palmieri, Rodrigo (BEPA. Boletim Epidemiológico Paulista, 2004)